MECHANISMS OF EPIDURAL CATHETER KNOTTING - V. A. Gluschenko; V. P. Kobrin; V. V. Repnikov; V. V. Kobrina (Вестник анестезиологии и реаниматологии, 2018)
The objective of the study: to determine factors and mechanisms of the epidural catheter knotting. Three clinical cases of the epidural catheter knotting have been studied, and 80 bench tests of catheters made of polyamide and polyether block amide have been run. It has been found out that the extension of the length in the inserted catheter and the speed of its extraction result in the higher risk of knotting. Polyether block amide catheters versus polyamide ones are safer respective the potential knotting, A certain algorithm of actions for a doctor has been offered in order to prevent knotting and breakage of the catheter.